Impact Of Electronic Marketing Tools, And Electronic Word Of Mouth On Online Purchase Intention: Empirical Study On University Students In Tabuk - baki, Hebatalla Mohsen Mohammed Abd el (The journal of contemporary issues in business and government, 2021)
This paper aims to study impactof electronic marketing tools, and electronic word of mouth on online purchase intention: empirical study on university Students in Tabuk, and also aim to study the different tools of Electronic marketing. The objective of this study is To examine the impact of E M tools on online purchase intention, the study aims to examine the impact of E W O M on online purchase intention, andto find out what is the most effective tool of E M impact on online purchase intention.The study was conducted in University of Tabuk in Saudi Arabia , the research hypotheses was adopted based on the previous studies, and Based on variables of the study . The researcher used the descriptive analytical method; The Data was collected through Field research (questionnaire) among 120 respondents. The results show there was a positive correlation between electronic marketing tools and online purchase intention among university students. This study recommends that companies should move away from conventional marketing techniques and inculcate electronic marketing into their marketing plans in order to better stay connected with customer.